Pemeriksaan Kesehatan Gigi Dengan Dmf-T Pada Siswa Siswi Kelas X Smp Makassar - Magfira, Magfira; Suprapti, Isma; Kusumastiti, Anisa Ramadhani; Prastyo, Eko; Aripa, Lusyana; Prehananto, Herlambang (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Dental and oral diseases that are a public health problem in general are in the supporting tissue of the teeth (periodontal diseases) and dental caries/cavities. This caries can be caused by various things between dental and oral health problems are important in health development, one of which is caused by the vulnerability of school-age children from dental health disorders. The purpose of Pengabdian kepada Masyarakat is to assess the status of dental and oral health in this case dental caries using the DMF-T value (decay, missing, filled, teeth). The DMF-T value is a number that indicates the number of teeth with caries in a person or group of people. The number d is a tooth that has a cavity due to dental caries, the number m is a tooth that has been extracted due to caries, the number f is a tooth that has been filled or filled due to caries and is in good condition. The method used in Pengabdian kepada Masyarakat activities is a direct examination of students who have become respondents. The results of community service, namely student knowledge, do not automatically encourage respondents to make efforts to maintain dental health properly and correctly, both in terms of maintaining a cariogenic diet or good and correct tooth brushing habits. The conclusion of this activity is that the DMF-T status of tooth decay in students is quite high, therefore it is necessary to do more education in preventing caries in early childhood.